INTRODUCTION TO GRASS JELLY CULTIVATION THROUGH THE URBAN FARMING CONCEOT FOR FAMILY WELFARE AND EMPOWERMENT GROUP OF RW IX, GRIYA BHAYANGKARA - Tarigan, Puji Lestari; Sasongko, Edi Purnomo; Aditya, Haidar Fari; Mindari, Wanti; Kusuma, Ramadhani Mahendra; Wijayanti, Fitri (Journal of Community Service, 2024)
Grass jelly is a popular plant in Indonesia. Various kinds of culinary preparations from grass jelly are developing in society. The benefits of grass jelly are very good for digestion, blood sugar, and preventing cancer. Grass jelly can be cultivated in narrow areas using polybags or pots. This method is a way that can be used to carry out agricultural activities in urban environments. The problem of narrow land can be handled by planting in containers and using ready-to-use media. This activity was carried out at RW IX, Griya Bhayangkara, Sidoarjo, East Java. The aim of this activity is to introduce the importance of PKK groups in urban areas to develop grass jelly plants because the benefits are very good and can be processed on a household scale. The methods used are lectures and practice. The type of grass jelly being developed is green grass jelly. According to the PKK group, grass jelly plants are very interesting to develop and have many benefits. For this reason, grass jelly plants are distributed to be cared for and harvested so they can be processed into various foods.